Genetic Code Expansion, Protein Expression, and Protein Functionalization in Bacillus subtilis - Scheidler, Christopher M; Vrabel, Milan; Schneider, Sabine (ACS synthetic biology, 2020)
The site-specific chemical modification of proteins through incorporation of noncanonical amino acids enables diverse applications, such as imaging, probing, and expanding protein functions, as well as to precisely engineer therapeutics. Here we report a general strategy that allows the incorporation of noncanonical amino acids into target proteins using the amber suppression method and their efficient secretion in the biotechnological relevant expression host Bacillus subtilis. This facilitates efficient purification of target proteins directly from the supernatant, followed by their functionalization using click chemistry. We used this strategy to site-specifically introduce norbornene lysine into a single chain antibody and functionalize it with fluorophores for the detection of human target proteins.
Keywords: CRISPR-Cas Systems; Protein Engineering; lysin; proteinové inženýrství; CRISPR-Cas systémy; Gene Expression Regulation, Bacterial; rekombinantní proteiny; genetické vektory; Isopropyl Thiogalactoside; Green Fluorescent Proteins; Bacillus subtilis; Lysine; norbornany; ELISA; Genetic Vectors; isopropylthiogalaktosid; Creatine Kinase, MM Form; Humans; Norbornanes; zelené fluorescenční proteiny; Genetic Code; regulace genové exprese u bakterií; kreatinkinasa, forma MM; Enzyme-Linked Immunosorbent Assay; genetický kód; Click Chemistry; lidé; Recombinant Proteins; click chemie